2021
DOI: 10.1021/jacs.1c09329
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizations with Elemental Sulfur: From Petroleum Refining to Polymeric Materials

Abstract: The production of elemental sulfur from petroleum refining has created a technological opportunity to increase the valorization of elemental sulfur by the synthesis of high-performance sulfur-based plastics with improved optical, electrochemical, and mechanical properties aimed at applications in thermal imaging, energy storage, self-healable materials, and separation science. In this Perspective, we discuss efforts in the past decade that have revived this area of organosulfur and polymer chemistry to afford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 147 publications
(329 reference statements)
0
137
0
1
Order By: Relevance
“…It has been demonstrated that inverse vulcanized polymers can be synthesized using a mechanochemical method. In the conventional thermal synthesis of inverse vulcanised polymers, the choice of potential crosslinkers is constrained to those that are miscible with molten sulfur as well as having sufficiently high boiling points 47 . The mechanochemical route removes these constraints.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that inverse vulcanized polymers can be synthesized using a mechanochemical method. In the conventional thermal synthesis of inverse vulcanised polymers, the choice of potential crosslinkers is constrained to those that are miscible with molten sulfur as well as having sufficiently high boiling points 47 . The mechanochemical route removes these constraints.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] In fact, the preparation of sulfur polymers is an innovative example of waste valorization given the fact that elemental sulfur is known for its globally distributed raw material reserves as a by‐product of the petroleum industry. [ 34 ] In a similar manner, usually the syntheses of the most elemental sulfur‐based polymers are acknowledged to be atom economical and often require no solvent. Moreover, the obtained polymeric materials are recognized to have a small environmental footprint.…”
Section: Sustainable Chemistrymentioning
confidence: 99%
“…In a typical polymerization, 70 : 30 wt% of S 8 to DIB are employed, which corresponds to molar feed ratios of 92 : 8 mol%, respectively, to afford a statistical copolymer of poly(sulfur‐ random ‐(1,3‐diisopropenylbenzene) (poly(S‐ r ‐DIB) composed of S−S units as linear fragments and S‐DIB−S units as branching units, in the idealized microstructure (Figure 2). Unambiguous structural characterization of S 8 derived copolymers is often challenging using standard techniques, such as, 1 H, or 13 C NMR spectroscopy due to the limited solubility of these materials with higher sulfur content [6,9] . Furthermore, these techniques do not report on the structure of sulfur catenation in the polymer backbone, or as end‐groups.…”
Section: Inverse Vulcanization: Copolymerizations In Liquid Sulfurmentioning
confidence: 99%
“…This new research area is at an intriguing nexus of petroleum, polymer and sustainability sciences, since S 8 is generated in large volumes from petroleum refining and has limited utility for other chemical products. Additionally, high sulfur content polymeric materials have been recently demonstrated to exhibit useful optical, electrochemical, metal scavenging, adhesive and flame retardant (FR) properties prompting further development of this field [8,9] . However, the synthetic polymerization chemistry to convert S 8 into well‐defined homopolymers, statistical and segmented copolymers remains fairly narrow in scope, which has limited the preparation of enhanced sulfur derived polymeric materials.…”
Section: Introductionmentioning
confidence: 99%